Public Access Centres in Uganda: The Past, Present and Future - Sulah, Ndaula (Technology & Social Change Group, University of Washington Information School, 2008)
The paper is based on the findings of Public access study conducted in Uganda as part of the broader study in 24 countries. It summarizes the methodology of the research, bringing out key findings with success factors and recommendations. It describes the country overview detailing its geography, political and geographic divisions, and demographic factors providing conclusions on the effects of each on Public Access. It provides a broader shape of the Public Access venues and centres in the country before focusing on the three main venues that target disadvantaged societies. It strategically examines Public Access venues from three angles; access, capacity and environment, which formed the framework of the study. The venues assessed include; community libraries, public libraries and multipurpose Community telecentre. The paper provides key recommendations, strategic areas for investment and direction for future research. It also highlights perceptions and changing media landscape especially with the introduction of ICTs.
Landscape Study, Uganda
This research focuses on the public access to information and communication landscapes in 24 countries, with specific focus on public libraries, to understand the information needs of underserved communities, public access to information and communication venues, and the role of ICT. Through field research in 24 countries conducted by local research partners, and cross-country comparative analyses based on common research design elements (see list of countries and research design overview in Appendix), the project aims to contribute to the knowledge in the field of information and ICT for development. Of particular interest and value are: the comparative look at key venues (libraries and other), and the mix of depth of in-country knowledge with breadth of global comparison to elicit success factors and scenarios to understand how diverse populations can and do access and use ICT to improve their lives. All outputs of this research will be broadly disseminated to interested stakeholders and placed in the public domain.
Keywords: Libraries, telecenters, telecentres, cybercafés, ICT4D, ICTD, Landscape Study, Public access venues, Access, capacity, environment and inequityUganda